Respuesta :

Answer:

Part A: D. [tex]y = (x + 1)(x+3)\\[/tex]

Part B: C. [tex]3x(x-3) = 0\\[/tex]

Step-by-step explanation:

For part A) we just have to plug in 0 for x and solve for y until we find the equation that says 3 is the value for y when x is 0. For purposes of speeding up the process the correct answer is D. I will show how to check for it now.

The equation: [tex]y = (x + 1)(x+3)[/tex]

Now plug in 0 for x.

[tex]y = (0 + 1)(0+3)\\[/tex]

Now solve.

y = (1)(3)

y = 3

This proves that this is the correct answer.

For part B) we just have to plug in the give values for x separately and check for each value of x that it equals 0. For the purpose of speeding up the process the correct answer is C. I will show how to check for it now.

The equation: [tex]3x(x-3) = 0[/tex]

Now plug in x for 0 and solve:

[tex]3* 0 (0-3) = 0\\[/tex]

[tex]0(-3) = 0\\[/tex]

[tex]0 =0\\[/tex]

This equation is true, now we check for the other value of x, 3.

[tex]3*3(3-3) = 0\\[/tex]

[tex]9(0) = 0\\[/tex]

[tex]0 =0\\[/tex]

This is also true so that means this is the correct answer.

ACCESS MORE